Host plant resistance of cassava green spider mite (CGM) (Mononychellus tanajoa Bondar) at IITA - Kanno, H.; Dixon, A.; Asiedu, Robert; Hahn, S.K. (1991)
Major upland soils in the humid and sub humid zones of West Africa consist of low activity clays (LAC) Alfisols, Ultisols and Oxisols. Alfisols which are less leached and have a high base saturation are more dominant in the sub-humid zone. Chemically they are more fertile, but they have a low structural stability. The Ultisols/Oxisols which are more prevalent in the humid zone, are less fertile, with major nutrient and acidity constraints. The major constraints on sustainable crop production on these soils, can be removed by proper seedbed and residue management, and by judicious fertilizer application and by liming amendments. These measures are needed to ensure the maintenance of adequate chemical, physical and biological fertility of the soils. Prototype technology research in West Africa that seeks to improve productivity and sustainability on these LAC soils has shown, that minimum tillage and/or alley-cropping are promising technologies for managing these soils. Further research is still needed to refine these systems and to identify alternative systems for the region.